Design, synthesis and biological evaluation of novel 1H-1,2,4-triazole, benzothiazole and indazole-based derivatives as potent FGFR1 inhibitors viafragment-based virtual screening - Jian Liu; Yu Wen; Lina Gao; Liang Gao; Fengjun He; Jingxian Zhou; Junwei Wang; Rupeng Dai; Xiaojing Chen; Di Kang; Lihong Hu (Taylor & Francis Group, 2020)
Fibroblast growth-factor receptor (FGFR) is a potential target for cancer therapy. We designed three novel series of FGFR1 inhibitors bearing indazole, benzothiazole, and 1H-1,2,4-triazole scaffold via fragment-based virtual screening. All the newly synthesised compounds were evaluated in vitro for their inhibitory activities against FGFR1. Compound 9d bearing an indazole scaffold was first identified as a hit compound, with excellent kinase inhibitory activity (IC50 = 15.0 nM) and modest anti-proliferative activity (IC50 = 785.8 nM). Through two rounds of optimisation, the indazole derivative 9 u stood out as the most potent FGFR1 inhibitors with the best enzyme inhibitory activity (IC50 = 3.3 nM) and cellular activity (IC50 = 468.2 nM). Moreover, 9 u also exhibited good kinase selectivity. In addition, molecular docking study was performed to investigate the binding mode between target compounds and FGFR1.